Applying the psychological empowerment theory to explore the youth ICT utilization of telecenters: The case study of Pusat Internet Desa (PID) Simpang Empat, Perlis - Yusop, Nor Iadah; Mohd Yusof, Shafiz Affendi; Sheik Osman, Wan Rozaini; Mat Aji, Zahurin (Universiti Utara Malaysia, 2011)
Digital technology is changing societies across the world. It is doing so by changing the power relationships that have structured those societies.Digital technology offers the potential to empower individuals by giving people more power as citizens and consumers in shaping their own lives. The information management literature presents empowerment as an important concept when assessing the impact of technology within organizations.For instance, the use of computer at workplace can positively empower users by bringing relevant information that eventually can improve their knowledge and performance.However, in the case of rural communities, the potential of empowering the communities is through the development of telecentres that provide a platform for acquiring various skills and knowledge.A telecentre is a public place where people can access computers, the Internet, and other digital technologies that enable people to gather information, create, learn, and communicate with others.Most importantly, it provides access to Information and Communication Technologies (ICTs) for people who cannot afford to own their own.Various telecentre projects have been piloted around the world and experiences have been documented such as in Malaysia.Under the Eight Malaysian Plan (2001-2005), the government has developed various types of rural telecentres to provide accessibility to the rural communities such as Pusat Internet Desa (PID), Medan InfoDesa (MID), and Kedai.Com.These various ICT-based infrastructures and initiatives are developed to help in reducing the digital gap between the rural and urban communities.Previous studies have indicated that empowerment is one of the issues that have been identified as part of the telecentre implementation challenges. Hence, the primary aim of this study is to examine the impact of telecentres’ implementation on individual empowerment. In order to describe the phenomenon, a conceptual framework is developed based on Zimmerman’ psychological empowerment (PE) theory in order to understand individual empowerment of the PID users, particularly on the adolescents aged between 18 to 25 years old.This research will be conducted using a descriptive and interpretive qualitative investigation of multiple-case study of PIDs.Data will be obtained using questionnaires, interviews, observations, and documentation reviews.This research is expected to contribute in filling the knowledge gap with regard to the human side of rural ICT development.Secondly, this research can contribute to a rich understanding of implementing and utilizing telecentres by producing rigorous evaluative evidence of the performance of rural telecentres. Essentially, the findings are expected to develop a more effective public policy and program planning particularly in terms of ICT for development policy and practice. Finally, the findings can also be used as evidence of PID program outcomes.Overall, the study is expected to provide a rich description of how telecentres’ implementation can help in empowering the young generation in a community.